A Metabolic Insight Into the Neuroprotective Effect of Jin-Mai-Tong (JMT) Decoction on Diabetic Rats With Peripheral Neuropathy Using Untargeted Metabolomics Strategy - Zhang, Qian; Song, Wei; Liang, Xiaochun; Xie, Jun; Shi, Yue; Shi, Xiaohu; Qiu, Bintao; Chen, Xiuting (Frontiers in Pharmacology, 2020)
Jin-Mai-Tong decoction (JMT) is a traditional Chinese compound prescription for treating diabetic peripheral neuropathy (DPN). The aim of this study was to investigate the neuroprotective effect of JMT on diabetic rats with peripheral neuropathy and to elucidate the potential mechanism based on a metabolomics approach. Sprague-Dawley (SD) rats were randomly into four groups: control group, Streptozotocin (STZ)-induced model group, JMT low dose (JMT-L) treated group and JMT high dose (JMT-H) treated group. After 12 weeks of treatment, behavioral changes, small fiber loss, and histopathological damages of sciatic nerve were estimated. Serum samples were collected for untargeted metabolomics analysis based on UPLC/QTOF-MS and multivariate statistics. As a result, JMT treatment at two dosages (13.9 and 27.8 g/kg·d) evidently improved the mechanical pain threshold (P < 0.05), increased the intraepidermal nerve fiber density (IENFD) and subepidermal nerve fiber density (SNFD) (P < 0.05), and renovated the demyelination and axonal atrophy of sciatic nerve in DPN rats. Furthermore, metabolomics study revealed that the serum metabolic profiles altered significantly among the control group and the STZ-induced model group. A total of 21 metabolites were identified as potential biomarkers that related to the therapeutic effect of JMT-H, while 15 of them were also recognized as biomarkers for JMT-L. These metabolites mainly involved in lipid metabolism, tricarboxylic acid (TCA) cycle, amino acid metabolism, and so on. Besides, correlation analysis indicated that both mechanical pain threshold and distal nerve fiber density were negatively correlated with the serum levels of metabolites involved in lipids metabolism and TCA cycle. In conclusion, the results demonstrated that JMT has an obvious protective effect against DPN, which could be mediated via holistic accommodation of the metabolic disorders in diabetic rats with peripheral neuropathy.